A portrait of U.S. firms that invest in R&D. Issue 1 (2nd January 2020) - Foster, Lucia; Grim, Cheryl; Zolas, Nikolas
ABSTRACT: This paper combines micro-level cross-sectional data from the Survey of Industrial Research and Development (SIRD) and the Business Research & Development and Innovation Survey (BRDIS) with the Longitudinal Business Database (LBD) to characterize U.S. firms that invest in research and development (R&D). The result is a firm-level panel data set from 1992 to 2013 that tracks firms as they enter and exit the R&D surveys. Using R&D expenditures to proxy R&D performance, we find that the majority of R&D is performed by large manufacturing firms that export, but the composition of R&D performing firms has gradually shifted more towards smaller nonmanufacturing firms. We find a high degree of persistence in R&D investment with previous R&D experience being a significant determinant of current R&D intensity, even after controlling for individual firm effects. We also uncover differences in observable firm characteristics between manufacturing and nonmanufacturing, as well as small and large, R&D performing firms.